Fidaxomicin: A Novel Agent for the Treatment of Clostridium difficile Infection - George G Zhanel; Andrew J Walkty; James A Karlowsky (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Due to the limitations of existing treatment options for Clostridium difficile infection (CDI), new therapies are needed.